2004
DOI: 10.1021/ja0390294
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl Sulfones:  Inhibitors of SrtA, a Transpeptidase Required for Cell Wall Protein Anchoring and Virulence in Staphylococcus aureus

Abstract: Several small molecule vinyl sulfones were found to exhibit irreversible time-dependent inhibition of the Staphylococcus aureus sortase SrtA in vitro. A representative of these compounds was shown to impair the ability of S. aureus bacteria to bind fibronectin-coated surfaces through in vivo inhibition of SrtA-mediated linkage of fibronectin to the cell surface. These data highlight the potential use of small molecule vinyl sulfones as chemotherapeutics to prevent adhesion to and colonization of host tissues d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(105 citation statements)
references
References 27 publications
2
101
0
2
Order By: Relevance
“…Earlier work used in vitro (inhibition of fluorogenic substrate cleavage) and virtual screening of compound libraries to identify sortase inhibitors (15,(52)(53)(54)(55)(56). Although these studies identified both competitive and noncompetitive inhibitors (57,58), isolated compounds have not yet been shown to inhibit in vivo sortase activity in staphylococci, i.e., the cleavage of sorting signals or the assembly of surface proteins into the bacterial cell wall (54,(59)(60)(61)(62). Many of the isolated compounds diminish or block staphylococcal growth, indicating that they cannot function as selective inhibitors of S. aureus sortase (53,61,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work used in vitro (inhibition of fluorogenic substrate cleavage) and virtual screening of compound libraries to identify sortase inhibitors (15,(52)(53)(54)(55)(56). Although these studies identified both competitive and noncompetitive inhibitors (57,58), isolated compounds have not yet been shown to inhibit in vivo sortase activity in staphylococci, i.e., the cleavage of sorting signals or the assembly of surface proteins into the bacterial cell wall (54,(59)(60)(61)(62). Many of the isolated compounds diminish or block staphylococcal growth, indicating that they cannot function as selective inhibitors of S. aureus sortase (53,61,63,64).…”
Section: Discussionmentioning
confidence: 99%
“…These peptide-derived inhibitors display favorable K i values, however their rates of inactivation are slow. Vinyl sulfones also react with thiols, but the corresponding peptide vinyl sulfones present even slower rates of sortase inactivation than diazoketone or chloromethylketone derivatives (17). Finally, phosphorous isosteres of peptides are effective transition state analogs and inhibitors of zinc proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of sortases by small molecules may therefore function as a therapeutic strategy for bacterial infections. Previous work described several sortase inhibitors, including methane-thiosulfonates (12), peptide substrate-derived affinity labels (13), natural compounds (14 -16), vinyl sulfones (17), diarylacrylonitriles (18), bis(indole) alkaloids (19), peptidomimetics (20), isoquinoline alkaloids (16), and threonine analogues (21). However, most of these compounds are either of low activity, lack specificity, or display undesirable structural features that confound therapeutic use.…”
mentioning
confidence: 99%
“…Sortase is also involved in the assembly of cell surface pili on Gram-positive bacteria, which often aid attachment to host cells (Ton-That & Schneewind 2003). Collectively, these and other findings suggest that sortases are promising targets for new antibacterial drugs (Schneewind et al 1993, Frankel et al 2004, Ton-That et al 2004, Weiss et al 2004, Zink & Burns 2005. However, there have been few studies focused on the development of specific inhibitors of sortases for the treatment of Gram-positive bacterial infections.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%